Political Budget Cycles in the Context of a Transition Economy: The Case of Albania - Endrit Lami (Comparative Economic Studies, 2022)
There is growing research on the political budget cycles in transition economies whose institutions, economies and societies differ significantly from those of developed countries. New democracies are more vulnerable to political budget (fiscal) cycles. Most studies focus on policy instruments (e.g. fiscal policies) rather than on macroeconomic outcomes. In this paper, we analyse the political budget/fiscal cycle in Albania, a transition post-communist country. We analyse monthly data on the budget balance (deficit). The findings show a strong difference in deficits during pre- and post-election quarters, which do not appear when econometric analysis is replicated on annually collapsed data. This paper highlights the importance of distinguishing between types of elections according to their outcomes. Electoral competitiveness (heightened incumbents' fear of elections loss), lower management efficiency, incumbent's carelessness about the budget situation during the mandate of political rivals and higher corruption can all be associated with elections that yield rotation (change of the party/coalition in power), thus resulting in a higher budget deficit.
Keywords: D72; E62; P16; H26; 330; Political budget cycles; Budget balance (deficit); Transition economies; Election outcomes